Entrepreneurial Orientation and Performance of Small-Scale Agribusiness Grain Farmers in North Rift, Kenya - Kebenei, Michael; Mathenge, Paul; Mwangi, Elias (European Journal of Business and Strategic Management, 2025)
Purpose: This study sought to determine the influence of entrepreneurial orientation and performance of small-scale agribusiness grain farmers in North Rift, Kenya. Further the study sought to determine the influence of entrepreneurial innovation, pro-activeness, risk-taking, competitive aggressiveness and autonomy on the performance of small-scale agribusiness grain farmers in North Rift, Kenya. Methodology: The study adopted the positivist research philosophy and descriptive survey research design was utilized. Target population included 497,737 small-scale agribusiness grain farmers in North Rift, Kenya. Yamane’s Formula of sample size determination was applied to derive a sample size of 400 respondents. Questionnaire was used for data collection. SPSS version 25 was applied in analyzing the data collected. The quantitative data comprised of the descriptive and inferential statistics. Descriptive statistics were summarized into percentages, mean and the standard deviation which was presented using figures, frequency tables and pie-charts. Inferential statistics were applied to test the hypothesis for the study. Findings: The findings showed that Innovation and performance of small-scale agribusiness grain farmers has a positive and significant relationship. Moreover, it was also established that pro-activeness, risk taking, competitive aggressiveness, and entrepreneurial autonomy significantly predicted the performance of small-scale agribusiness grain farmers in North Rift, Kenya. Entrepreneurial characteristics had a statistically significant moderating effect on the relationship between entrepreneurial orientation and performance of small-scale agribusiness grain farmers in North Rift, Kenya. Unique Contribution: The study recommended , small-scale grain farmers to embrace entrepreneurial orientation, research institutions to contact regular market research, government institution to enact policies that support entrepreneurial orientation and training institutions to contact educational training, there is a need for educational institutions to integrate entrepreneurial innovativeness, risk management, pro-activeness, competitiveness, business autonomy and entrepreneurial characteristic into agricultural curricula to equip future farmers with the necessary skills.